Bibliometric Analysis of the Field of Entrepreneur Formation - Virgen Ortiz, Viviana; Cobo Oliveros, Carlos Eduardo; Betancourt Guerrero, Benjamin (Cuadernos de Administración, 2014)
This work presents the results of a bibliometric analysis in the field of entrepreneur formation, which permit conducting a diagnosis of the evolution and current state of the theme. The methodology employed consists in the construction and subsequent analysis of quantity and quality bibliometric indicators, as well as an analysis of the topological structure of the networks of authors, observing its temporal evolution during the interval between 2003 and 2013. As a result, a growing field is found characterized by scarce citations among the authors, lack of integration among the researchers, and absence of development based on support disciplines